Integrasi Lean DMAIC dan Circular Economy untuk Reduksi Waste pada Manufaktur Paving Block - Retnowati, Dini; Fudhla, Ahmad Fatih; Puspita, Asri Dwi; Annurrada, Sofia (Jurnal Serambi Engineering, 2025)
Waste is a significant challenge in the manufacturing industry, including small and medium enterprises (SMEs) engaged in paving block production. This study applies the Lean DMAIC (Define–Measure–Analyse–Improve–Control) methodology to identify, analyze, and reduce waste in the production process. A case study was conducted at a paving block factory in East Java, which has an annual production capacity of 119,400 m². Data were collected from production records, observations, and interviews conducted between September 2024 and August 2025. Analysis using a weighted Pareto diagram and Flow Process Mapping revealed that defect categories, although accounting for only 1.99% of total production, resulted in a significant accumulation of dead stock in the storage area. Through a Decision Matrix and a radar chart, a recycling strategy was selected as the improvement solution. This strategy was subsequently formalized into a Standard Operating Procedure (SOP) for managing rejected products, ensuring consistent implementation and adherence. Evaluation of the implementation over one month showed a 23.8% reduction in dead stock volume. These findings provide empirical evidence of the effectiveness of integrating Lean DMAIC with circular economy principles in the paving block industry, offering a practical framework that can be replicated in similar manufacturing sectors.